THE PATH TO ENTREPRENEUR: UNDERSTANDING THE FACTORS BEHIND ENTREPRENEURIAL INTENTION - Simanjuntak, Salomo Michihiro; Komalasari, Farida (Proceeding of the International Conference on Family Business and Entrepreneurship, 2024)
Indonesia's entrepreneurship ratio in 2022 is 3.18% of Indonesia's total population.  This figure is lower than Thailand (4.2%), Malaysia (4.7%), and Singapore (8.7%).  Meanwhile, the Ministry of Cooperatives and MSMEs targets the entrepreneurship ratio in 2024 to increase to 3.95%. To achieve this target, appropriate strategy formulation is required.  In order to develop this strategy, policy maker needs information about the factors that influence Indonesian entrepreneurial intention.  Therefore, research is needed on the factors that influence Indonesian entrepreneurial intention.  This research analyzes factors of Indonesian entrepreneurial intention, those are entrepreneurial self-efficacy, entrepreneurship education, risk-taking propensity, and internal locus of control with self-efficacy as mediating variable. Using a quantitative approach, this research gathers data from 138 aspiring entrepreneurs, which are selected by using snowball sampling.  Structural Equation Modelling – Partial Least Square (SEM-PLS) is used to test the hypoyhesis.The results indicate that risk-taking propensity does not significantly impact entrepreneurial intention, whereas entrepreneurial self-efficacy, entrepreneurship education, and internal locus of control are significantly impact entrepreneurial intention.  Moreover, entrepreneurial self-efficacy partially mediates the influence of entrepreneurship education toward entrepreneurial intention. These findings highlight the importance of self-efficacy and educational support in influencing Indonesian entrepreneurial intention. From a practical standpoint, to increase Indonesian entrepreneurial intention, enhancing self-efficacy by setting clear goals, maintaining perseverance, and focusing on critical tasks are recommended. Additionally, fostering an internal locus of control and leveraging comprehensive entrepreneurship education are crucial for supporting entrepreneurial ambitions. Governments and educational institutions should provide both theoretical and practical resources to better cultivate entrepreneurial skills.  This research offers valuable insights into the factors affecting entrepreneurial intention, enriching the understanding of how to effectively support new business ventures to increase the entrepreneurship ratio in Indonesia.